Assistance of Posyandu Cadres in Implementing Massage and Monitoring Infant Growth and Development through Augmented Reality Application - Irma Maya Puspita; Wardah Suweleh; Ponidi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Infant health in the early stages of life is greatly influenced by various factors, including proper monitoring of growth and development and providing optimal stimulation. One form of beneficial stimulation is baby massage, which has been proven to help the physical and emotional development of infants. However, the limited knowledge and skills of Posyandu cadres often become an obstacle in providing maximum service. This article examines the implementation of an Augmented Reality (AR)-based application to support Posyandu cadres in guiding infant massage and monitoring infant growth and development at Posyandu. The results of the study indicate that the AR application can improve cadres' knowledge and skills in performing infant massage, as well as help parents understand child growth better. This article also provides recommendations regarding the implementation of the AR application as a technological innovation in Posyandu services.